Housing discrimination and racial cancer disparities among the 100 largest US metropolitan areas - Beyer, Kirsten M. M. (Cancer, 2019)
PURPOSE: Cancer contributes substantially to the life expectancy gap between US Blacks and Whites, and racial cancer disparities remain stubborn to eradicate. Disparities vary geographically, suggesting that they are not inevitable. METHODS: We examined the relationship between housing discrimination and the size of cancer disparities across large US metropolitan statistical areas (MSAs). We measured MSA level cancer disparities using Centers for Disease Control data. We estimated mortgage discrimination for each MSA using the Home Mortgage Disclosure Act database, and MSA racial segregation using US Census data. We mapped patterns of housing discrimination and cancer disparities and measured the associations between these place-based factors and cancer disparities across MSAs. RESULTS: Black-to-White cancer mortality disparities (rate ratios) vary geographically, ranging from 1.50 to 0.86; 88% of mortality ratios are above 1, indicating higher mortality for Blacks. In areas with greater mortgage discrimination, the gap between Black and White cancer mortality rates is larger (r=0.32, p=0.001). This relationship persists in sex-specific analyses (males: r=0.37, p<0.001, females: r=0.23, p=0.02) and in models controlling for confounders. In contrast, segregation is inconsistently associated with disparities. Adjusting for incidence disparities attenuates, but does not eliminate, the correlation between mortgage discrimination and mortality disparities (r=0.22–0.24), implying that cancer incidence and survival each account for part of the mortality disparity. CONCLUSION: Mortgage discrimination is associated with larger Black-to-White cancer mortality disparities. Some areas are exceptions to this trend. Examination of these exceptions, and policies related to housing discrimination, may offer novel strategies for explaining and eliminating cancer disparities.